Analisis Wacana Kritis Model Teun A. Van Dijk Terhadap Pemberitaan Mediasi Prabowo Dalam Konflik Iran-As-Israel - Laila Adisti Aulia; Nabila Aswari Lubis; Rachel Esteria Siagian; Ruth Sofia Rolenza Lumbanraja; Wina Etami; Mara Untung Ritonga (CV. SINAR HOWUHOWU, 2026)
This study uses Teun A. van Dijk's Critical Discourse Analysis model to examine the media framing of President Prabowo Subianto's mediation offer in the Iran-US-Israel conflict in early March 2026. Six news articles from Kompas.com, Tempo.com, and Kumparan.com were analyzed through three dimensions: discourse structure (macro, superstructure, micro), social cognition, and social context. The analysis results show different framing patterns: Kompas.com emphasizes diplomatic balance accompanied by realistic skepticism of American dominance; Tempo.co highlights political pragmatism and doubts about its effectiveness; while Kumparan.com displays strong support from Iran while sharply criticizing that the initiative is unrealistic due to US hegemony. Overall, the media discourse reflects Indonesia's independent, active, and neutral foreign policy, but is influenced by domestic political interests and global power dynamics. This study contributes to the understanding of media framing in geopolitical crisis situations and the development of van Dijk's model in the context of Indonesian digital journalism.